INFORMATION RESOURCE ASSESSMENT: A STUDY OF DIGITAL AND TRADITIONAL LIBRARY ENVIRONMENTS - Ahmad Bakeri, Abu Bakar; Kaba, Abdoulaye (Malaysian Journal of Library and Information Science, 2002)
Assessing and evaluating information resources is necessary for the improvement of library services. Recently, Malaysian libraries have witnessed a growing utilization of digital technology in the provision of library services, coupled with the emergence of the Internet-based digital libraries. Although the trend is timely, the cost-effectiveness of its adoption is unknown. As libraries with sizable collection development budgets are having difficulties in coping with escalating price of electronic collection, the need to assess these information resources is necessary and critical. This study aims to assess the information resources in the digital and traditional library environments. Four Malaysian libraries; Majlis Perbandaran Subang Jaya (MPSJ) Hypermedia Library, Majlis Perbandaran Petaling Jaya (MPPJ) Library, International Islamic University Malaysia (IIUM) Library and Multimedia University (MMU)) Library, at Cyber Jaya Compus are selected for the study. Issues such as collection building, electronic collection, cost and circulation are examined.